Studi Gender: Partisipasi Publik dan Penguatan Individu Rumah Tangga - Yusriani, Eni Ria; Qistina, Selamah Rabia (Saree: Research in Gender Studies, 2023)
The conservative paradigm prevalent in society perceives the role of women as suboptimal both in domestic life and in the public sphere. Therefore, this research aims to thoroughly examine the contributions of women in household and societal contexts. The research is conducted in the form of a literature review. Data is gathered from 40 research journals using keywords such as gender, public policy, household, and Islamic values. The data is then processed using data reduction to generate a comparative analytical model. The research findings indicate that the contributions of women in domestic life can be observed through the formation of character values in children. Character values are categorized into terminal and instrumental values. On the other hand, in the public sphere, when facilitated by the government or supported by the family, women are able to contribute to economic strengthening and other social movements. The indication towards these categories of women's values is based on Islamic ethics, which states that women have equal value and position as men. The findings also determine the "oughtness" or obligation from both categories of values. The research results show that generally, both adolescents and parents exhibit good instrumental and terminal values.   Abstrak Paradigma konservatif yang berkembang di masyarakat menganggap peran perempuan kurang optimal baik di dalam kehidupan rumah tangga maupun ranah publik. Oleh sebab itu penelitian bertujuan mengkaji secara mendalam kontribusi perempuan di dalam rumah tangga dan masyarakat. Penelitian berjenis studi pustaka. Data diambil dari 40 jurnal penelitian menggunakan kata kunci gender, kebijakan publik, rumah tangga, dan nilai KeIslaman. Data kemudian diolah menggunakan reduksi data sehingga mampu menghasilkan konstruk model yang dianalisis secara komparatif. Hasil penelitian menunjukkan kontribusi perempuan di dalam kehidupan rumah tangga dapat diamati melalui pembentukan nilai-nilai karakter anak. Nilai karakter dikategorikan menjadi nilai terminal dan instrumental. Sedangkan di dalam ranah publik apabila difasilitasi oleh pemerintah maupun dukungan keluarga perempuan mampu berkontribusi dalam hal penguatan ekonomi dan gerakan sosial lainnya. Indikasi terhadap kategori nilai perempuan ini didasarkan  dengan etika Islam bahwa peran dan kedudukan wanita dengan laki-laki sama secara nilai. Hasil juga menentukan 'oughtness' atau 'kewajiban' dari kedua kategori nilai tersebut. Hasil penelitian menunjukkan bahwa secara umum, baik remaja maupun orang tua memiliki nilai instrumental dan terminal yang baik.